Question
upstudy study bank question image url

if \( g(1)=4 f(2)=2, f^{\prime}(2)=g^{\prime}(1)=-1 \) \( h(x)=\frac{1}{f(x)}+g\left(\frac{2}{x}\right)+x \Rightarrow h^{\prime}(2)= \) ?

Ask by Ray Watson. in Iran
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( h'(2) = \frac{7}{4} \)

Solution

To find \( h'(2) \) for the function \[ h(x) = \frac{1}{f(x)} + g\left(\frac{2}{x}\right) + x, \] we'll differentiate \( h(x) \) with respect to \( x \) and then evaluate at \( x = 2 \). 1. **Differentiate each term:** - The derivative of \( \frac{1}{f(x)} \) is \( -\frac{f'(x)}{[f(x)]^2} \). - The derivative of \( g\left(\frac{2}{x}\right) \) using the chain rule is \( g'\left(\frac{2}{x}\right) \cdot \left(-\frac{2}{x^2}\right) \). - The derivative of \( x \) is \( 1 \). 2. **Combine the derivatives:** \[ h'(x) = -\frac{f'(x)}{[f(x)]^2} + g'\left(\frac{2}{x}\right) \cdot \left(-\frac{2}{x^2}\right) + 1. \] 3. **Evaluate at \( x = 2 \):** - Given: \( f(2) = 2 \), \( f'(2) = -1 \), \( g'\left(1\right) = -1 \) (since \( \frac{2}{2} = 1 \)). \[ h'(2) = -\frac{f'(2)}{[f(2)]^2} + g'\left(1\right) \cdot \left(-\frac{2}{2^2}\right) + 1. \] Substitute the known values: \[ h'(2) = -\frac{-1}{2^2} + (-1) \cdot \left(-\frac{2}{4}\right) + 1 = \frac{1}{4} + \frac{1}{2} + 1 = \frac{7}{4}. \] **Final Answer:** \(\boxed{\dfrac{7}{4}}\)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To find \( h'(2) \), we start by computing the derivative of \( h(x) \). We have: \[ h(x) = \frac{1}{f(x)} + g\left(\frac{2}{x}\right) + x \] Applying the product, chain, and sum rules, the derivative \( h'(x) \) can be computed as follows: \[ h'(x) = -\frac{f'(x)}{(f(x))^2} + g'\left(\frac{2}{x}\right) \cdot \left(-\frac{2}{x^2}\right) + 1 \] Now, substituting \( x = 2 \): \[ h'(2) = -\frac{f'(2)}{(f(2))^2} + g'\left(1\right) \cdot \left(-\frac{2}{2^2}\right) + 1 \] We know: \( f(2) = 2 \), hence \( (f(2))^2 = 4 \) Additionally, we know \( f'(2) = -1 \) and \( g'(1) = -1 \): \[ h'(2) = -\frac{-1}{4} + (-1) \cdot \left(-\frac{2}{4}\right) + 1 \] Simplifying, we find: \[ h'(2) = \frac{1}{4} + \frac{2}{4} + 1 = \frac{1}{4} + \frac{1}{2} + 1 = \frac{1}{4} + \frac{2}{4} + \frac{4}{4} \] This gives us: \[ h'(2) = \frac{7}{4} \] Thus, the final result is: \[ h'(2) = \frac{7}{4} \]

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy